1999
DOI: 10.1007/s001980050221
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Architecture in the Distal Radius Using Magnetic Resonance Imaging in Subjects with Fractures of the Proximal Femur

Abstract: To determine whether magnetic resonance (MR)-derived measures of trabecular bone architecture in the distal radius are predictive for prevalent hip fractures, 20 subjects with hip fractures and 19 age-matched postmenopausal controls were studied. Bone mineral density (BMD) measures at the hip (dual-energy X-ray absorptiometry, DXA) and the distal radius (peripheral quantitative computed tomography, pQCT) were also obtained. We compared the MR-based structural measures derived in the radius with those in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(140 citation statements)
references
References 26 publications
12
122
2
4
Order By: Relevance
“…This study may have been underpowered to accurately assess these other mircoarchitecture outcomes and further investigation is needed. Observational imaging studies in adults with a fracture history have demonstrated that reduced bone strength may be influenced by deficits in the trabecular bone network (10,19,24). In particular, the size of the holes in the trabecular network at appendicular skeletal sites can provide information about bone structural competence (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study may have been underpowered to accurately assess these other mircoarchitecture outcomes and further investigation is needed. Observational imaging studies in adults with a fracture history have demonstrated that reduced bone strength may be influenced by deficits in the trabecular bone network (10,19,24). In particular, the size of the holes in the trabecular network at appendicular skeletal sites can provide information about bone structural competence (40).…”
Section: Discussionmentioning
confidence: 99%
“…Hole size analyses do not depend on any stereologic assumptions, whereas the derivation of Tb.Sp, Tb.Th, and Tb.N does indeed depend on sterologic assumptions (i.e., parallel plate model) (35). Moreover, some suggest that comprehensive imaging studies aiming to determine histomorphometric differences between groups should have at least 50 participants per group to provide sufficient power (19). Burghardt and colleagues also found no differences in radius microarchitectural indices, including Tb.N, in a smaller pilot study in women with type 2 DM and age-and height-matched healthy controls using pQCT (47).…”
Section: Pritchard Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…A further potential motivation is the study of the structural manifestations of metabolic bone disease such as renal osteodystropy (166). Evidence for these developments is the rapid growth of the clinical literature (8,83,84,127,145,165,(167)(168)(169)(170)(171)(172) and also, to a lesser extent, the increased use of CT to characterize TB (14)(15)(16)(173)(174)(175)(176)(177).…”
Section: Clinical Applications Of Trabecular Bone Microstructural Anamentioning
confidence: 99%
“…There is now clear evidence that the findings from histomorphometry, suggesting that inclusion of structural parameters substantially improves the discrimination of patients with osteoporotic fractures from their unfractured peers, is equally true for measurements obtained in vivo at much lower resolution (83,127,168,169). At least three studies provide compelling evidence for the independent role of architecture as a predictor of bone strength.…”
Section: Clinical Applications Of Trabecular Bone Microstructural Anamentioning
confidence: 99%